2013
DOI: 10.2519/jospt.2013.4792
|View full text |Cite
|
Sign up to set email alerts
|

Manual Physical Therapy and Exercise Versus Supervised Home Exercise in the Management of Patients With Inversion Ankle Sprain: A Multicenter Randomized Clinical Trial

Abstract: Study Design Randomized clinical trial. Objective To compare the effectiveness of manual therapy and exercise (MTEX) to a home exercise program (HEP) in the management of individuals with an inversion ankle sprain. Background An in-clinic exercise program has been found to yield similar outcomes as an HEP for individuals with an inversion ankle sprain. However, no studies have compared an MTEX approach to an HEP. Methods Patients with an inversion ankle sprain completed the Foot and Ankle Ability Measure (FAAM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
74
0
8

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(93 citation statements)
references
References 57 publications
(77 reference statements)
5
74
0
8
Order By: Relevance
“…In comparative effectiveness studies of the addition of MT to a comprehensive rehabilitation program, patients improved at earlier time points as compared to the exercise-centric control interventions. 1,7,23 Patients who return to function quicker are likely to be discharged from care sooner, which could explain the decreased health care utilization and cost in this treatment group.…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In comparative effectiveness studies of the addition of MT to a comprehensive rehabilitation program, patients improved at earlier time points as compared to the exercise-centric control interventions. 1,7,23 Patients who return to function quicker are likely to be discharged from care sooner, which could explain the decreased health care utilization and cost in this treatment group.…”
Section: Limitationsmentioning
confidence: 99%
“…31 Distinct patients who were billed for 1 or more of these 3 CPT codes were counted only once in comprehensive rehabilitation program, is more effective in reducing pressure pain thresholds and improving function in patients with PF when compared to comparative interventions. 1,7,20,23,26 Despite the growth of evidence for MT and supervised rehabilitation in recent years, practice patterns often lag behind published evidence. 15 This gap between evidence and practice is multifactorial and may be attributed to a clinician's access to the evidence, 15,27 difficulty appraising the evidence, 15,27 interest and perceived role in utilizing evidence, 27 and poor self-efficacy due to lack of training or comfort level with searching, analyzing, and implementing evidence.…”
mentioning
confidence: 99%
“…Improvements in both studies were reportedly retained 1 month and 6 months beyond the treatment period, suggesting that TJM may have a long-term effect on recovery from inversion ankle sprain. 1,4 The technical descriptions of TJM were similar between the studies. All of the authors reported placing patients in a supine position with the knee in full extension and applying the manipulative thrust in a caudal direction.…”
Section: Implications For Practice Education and Future Researchmentioning
confidence: 90%
“…1,4,5 These studies, summarized in Table 1, were all RCTs. All 3 studies investigated the efficacy of TJM on patients with a history of inversion ankle sprain.…”
Section: Results Of Searchmentioning
confidence: 99%
See 1 more Smart Citation